KONSEKUEN IKLIM KEADILAN DENGAN KEPERCAYAAN SEBAGAI PEMEDIASIAN: PENDEKATAN MULTIFOCI DAN ANALISIS LINTAS LEVEL - , RATNO PURNOMO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The main objective of this research was to examine the cross-level effect of justice climate on individual attitudes and behaviors. Multifoci approach and target similarity model with mediating factors are considered in testing the cross level effect. Justice dimensions used in the study are procedural and interactional justice with foci organization and supervisor. So, there were four dimension of justice climate consists of procedural justice climate foci organization, interactional justice climate foci organization, procedural justice climate foci supervisor, and interactional justice climate foci supervisor. Mediating factor used are the trust to organization and trust to supervisor. Individual behavior used as outcomes are proactive behavior and deviance behavior. Deviance behaviors consist of two dimensions, organizational deviance and interpersonal deviance. Social exchange theory, organizational climate, and group value model used as a basic for hypotheses development. The research was conducted using a survey research design in four organizations with a total number of 399 respondents from 50 work units. Justice climate measured at the unit level and tested using interrater agreement (IRA) and intraclass correlation (ICC). Trust, proactive behavior and deviance behavior were measured at the individual level. Hierarchical linear modeling (HLM) was used to test the cross-level effect of justice climate on individual trust, proactive behavior and deviance behavior, and HLM 2-1-1 model is used to examine the effect of cross-level with mediating factor. Important empirical contribution of this research is cross-level effect of justice climate on individual behavior with trust as mediating factors. The results showed that multifoci-mediated model is not supported as a whole, but multidimensionalmediated model with foci organization empirically supported. Trust to organization mediated the effect of procedural and interactional justice climate on proactive behavior and deviance behavior, whereas trust to supervisor does not have a role as a mediating factor.